Penerapan Logika Fuzzy Menggunakan Metode Mamdani Pada Prediksi Jumlah Kasus Positif Covid-19 - Graha Prakarsa; Vani Maharani Nasution (STMIK Budi Darma, 2021)
The Covid-19 pandemic has caused many hospitals around the world to experience difficulties both in terms of management and infrastructure advice in providing services because the number of patients soared in a short time so that treatments such as providing services, facilities, and medical personnel were unpredictable. Therefore, we need an application that can predict the number of positive Covid-19 cases 14 days later to help the Covid-19 Handling Acceleration Task Force team in order to provide the right policies for handling the provision of services, facilities, and medical personnel. Fuzzy logic that can be used to analyze Covid-19 problems that contain uncertainty at this time. The research conducted to design the system was obtained from the observation of existing data, in this study using descriptive research methods. The results of this study conclude that the fuzzy logic of the Mamdani method in predicting the number of positive cases of COVID-19 in West Java Province has an error rate of 50.16%. The application of fuzzy logic in predicting the number of positive cases of covid-19 uses the fuzzy logic model of the mamdani method to predict the number of positive cases of covid-19 in West Java Province with an error rate of 50.16%